The effect of shade on the biological control of Salvinia molesta D.S. Mitchell [Salviniaceae] by the weevil, Cyrtobagous salviniae Calder and Sands [Curculionidae] - Maseko, Zolile (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
Salvinia molesta, a floating aquatic weed, is a global menace in many water bodies and waterways. The weed disrupts the ecological balance wherever it invades and also has wide ranging economic and health impacts. Its impact has resulted in the need to control it, and while chemical and mechanical control are often ineffective, biological control by the weevil Cyrtobagous salviniae is largely successful. However, in many parts of the world, including South Africa, biological control of S. molesta has been less effective where the weed grows as an understory species. Shallow and shaded waters characteristically found at the margins of water bodies provide a refuge for S. molesta. Therefore, the aim of the study was to determine the effect of shade on the efficacy of biological control of S. molesta. Investigations into the problems associated with control in the shade were carried out in a greenhouse and in the field. In controlled greenhouse experiments, plants were grown at high and low nutrient levels in individual mesocosms, at three varying levels of shade, where half the mesocosms were inoculated with C. salviniae. Plants in high nutrient conditions were significantly more productive in terms of biomass accumulation, compared to those grown at low nutrient levels, in both the absence and presence of herbivory at all levels of shade tested. Plants grown in the shade and in high nutrient conditions had significantly higher quality compared to the ones exposed to full sun. Higher plant quality in the shade consequently resulted in accelerated fecundity for C. salviniae resulting in significantly higher weevil populations. Furthermore, less damage was recorded on plants in the shade, possibly due to the high nitrogen concentrations which may have deterred grazing by C. salviniae. However, in the absence of shading, plants were of lower quality and consequently sustained more damage from herbivores despite lower weevil populations. In contrast to the greenhouse, there were no differences in biomass recorded in the field at two nutrient levels and in the presence of herbivory for both shade and open sites. Nutrients added to high nutrient treatment quadrats diffused evenly across the water body resulting in uniform nutrient distribution, hence uniform plant biomass and carbon-nitrogen ratio. Despite the lack of statistical differences, more weevils were found in the full sun plots, while modest populations were recorded in the shade. Higher weevil populations consequently led to more damage in the sun, a situation that has been observed in most field sites in South Africa. The results therefore suggest that nutrients were pivotal in plant growth compared to light regimes (amount of PAR). Plant quality significantly influenced weevil populations and plant damage in both studies, demonstrating that plant nitrogen plays a crucial role in the plant- herbivore system. Furthermore, in both the greenhouse and field, despite lack of statistical differences, plants exposed to full sunlight suffered more damage than shade plants, pointing towards better control in the sun compared to the shade, suggesting that there is greater preference of sun-exposed plants for grazing by the weevils. The results from this study add to the growing body of literature that plant quality is a major factor in determining the success of aquatic weed biological control programmes.
Keywords: Salvinia molesta; Aquatic weeds -- Biological control; Beetles; Insects as biological pest control agents